2018
DOI: 10.1021/acs.jced.8b00810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Sodium Chloride on Tetra-n-butylammonium Chloride Semiclathrate Thermal Stability at Atmospheric Pressure

Abstract: Tetra-n-butyl ammonium chloride (TBAC) is known to form semiclathrate cages when dissolved in water. Melting points determined using differential scanning calorimetry (DSC) were used to create a phase diagram for the binary TBAC−H 2 O semiclathrate system from 0 to 8 molal TBAC at atmospheric pressure. This phase diagram shows the existence of TBAC semiclathrate cages with a congruent melting point at about 286.8 K at approximately 2 molal TBAC as well as the existence of a TBAC−H 2 O eutectic mixture of unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(47 citation statements)
references
References 36 publications
13
34
0
Order By: Relevance
“…The DSC cooling thermograms for binary solutions of TBAC-H 2 O were obtained at concentrations ranging from 0 to approximately 7.775 molal TBAC, respectively (data not shown). Similar to the results of Siddiq et al, 23 the cooling thermograms showed that pure water does not have a normal freezing transition at 273.15 K. Instead, sharp freezing transitions which occurred at various temperatures near ∼251.5 K were observed. They explained this as a rapid and sudden transition due to the freezing of ultrapure, supercooled, free, bulk water.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The DSC cooling thermograms for binary solutions of TBAC-H 2 O were obtained at concentrations ranging from 0 to approximately 7.775 molal TBAC, respectively (data not shown). Similar to the results of Siddiq et al, 23 the cooling thermograms showed that pure water does not have a normal freezing transition at 273.15 K. Instead, sharp freezing transitions which occurred at various temperatures near ∼251.5 K were observed. They explained this as a rapid and sudden transition due to the freezing of ultrapure, supercooled, free, bulk water.…”
Section: Resultssupporting
confidence: 88%
“…Determination of the Purity TBAC by Precipitation with AgNO 3 . Gravimetric silver chloride analysis was utilized to determine the purity of TBAC by precipitation of AgCl of the dissolved TBAC samples using AgNO 3 using the same technique by Siddiq et al 23 2.4. Determination of the Concentration of the TBAC Stock Solution.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 3 more Smart Citations